Sustainable Smart Waste Management System - Jayawardena, S.; Subhashini, K.K.P. (NSBM Green University, 2021)
This is an era where technology is predominating every aspect of the world, competitive market on economic world is widening to a greater scale resulting significant achievements to mankind and simultaneously creating much more chaotic conditions in terms with nature and its elements by humans. Especially waste management has become a major issue worldwide from developed nations to developing nations. Therefore, Sri Lankan waste management can be considered as an important social need.Will Clean is a systemthat enables the Sri Lankan waste management strategy to step into a sustainable approach via modern technology, this system reaches to the Most importantly Will Clean will systematically segregate Degradable and Non – Degradable waste into two segments within the system for the convenience of the users, by letting the residents (Users) to sell their Non – Degradable waste to the Waste buyers via the mobile application under distinct categories such as, Plastic, glass, metal and significantly the E – Waste. Resulting an E –Platform for the users to sell their waste which had been dumped in unhealthy manner for past decades causing many environmental issues. Furthermore, this system allows the residents to communicate with their relevant governing authority to have an efficient track on collecting non-Degradable waste by building a connection between the mobile and web applications. Finally, Will Clean will establish sustainability, efficiency and environmental conversation with economical enhancement in the local society to address wider issues such as global climate change, household economy and public hygiene and Will Clean can be deemed as a timely need for the current society. Furthermore, Wil Clean can be presented as one of the very innovative solutions to a major problem that can be considered as a threat to mankind, that is none other than global waste management issue, which has triggered numerous socio-economic and health problems locally and globally. This global hazard can be addressed by the local initiative of Will clean as it is a Smart Waste Management System that enables efficient management of waste in a systematic approach and its importance can be deemed as “With rapid increase in population, the issues related to sanitation with respect to garbage management are degrading immensely. It creates unhygienic conditions for the citizens in the nearby surrounding, leading to the spread of infectious diseases and illness. To avoid this problem, IoT based “Smart Waste Management” is the best and trending solution.Moreover, Will Clean is functioning in two different approaches to degradable waste and non-degradable waste as it is expanding its functions to the upliftment of domestic economy by creating a portal for any user to engage in a non-degradable waste market for selling and buying them, simultaneously this project enforces a systematic governance over degradable waste collection to recycling. Importantly, Will Clean directly involves in the battle against Climate Change by working on reducing the accumulation of non-degradable waste into nature from urban, sub-urban and rural human habitats in Sri Lanka. Furthermore, Will Clean Smart Waste Management System endorse the Sustainable Development Goals of United Nations (SDG – UN) by empowering key factors. Finally, will clean can be introduced as a timely need for the 21st Century as a sustainable and lively tool for a good living standard to global citizens.
Keywords: Smart waste management; Degradable